Understanding the added worker effect: A multiple methods interpretation - Heather Laurie; Karon Gush; James Scott; Mark Bryan; Simonetta Longhi (University of Essex, Institute for Social and Economic Research (ISER), 2015)
This paper provides an integrated interpretation of qualitative and quantitative data examining how couples respond when one partner loses their job. According to economic theory there may be an 'Added Worker Effect' where, when one partner loses their job, their spouse enters the labour market or takes on additional hours to compensate. The paper uses a multiple methods approach to gain a fuller understanding of couples' responses pre and post the UK Great Recession and to explore the factors influencing couples' decision-making process when experiencing a job loss. The paper is therefore a synthesis of findings produced by quantitative and qualitative elements of the same project and aims to explore where the findings from each methodological strand of the research can contribute to a better understanding of the dynamics of household decision making and couple's labour supply responses to job loss.
Keywords: J22; J64; 330; couple-households; household labour supply; added-worker effect; recession; employment; mixed methods research